Counseling with Tooth Brushing Demonstration Method as an Effort to Improve Tooth Brushing Skills and the Status of Dental and Oral Hygiene in Early Childhood at School (Medico Legal Update, 2021)
Dental health problems suffered by many people in Indonesia is dental caries. Poor dental and oral hygieneis one of the factors causing dental caries or oral and dental health problems. Teaching oral health withdemonstration method can improve tooth brushing skills and reduce oral and dental hygiene in earlychildhood. This study aims to the effectiveness of counseling with brushing demonstration method as aneffort to improve tooth brushing skills and the status of dental hygiene in early childhood in school. Method:this study used a quasy experiment with a pretest and posttest with one group design. This research wasconducted at Kindergarten Dharma Putra Nusantara 86 Cilandak District, South Jakarta City. Independentvariable: counseling by demonstration method and the dependent variable: brushing skills and the statusof early childhood dental and oral hygiene. Data were tested using Wilcoxon. Results: counseling with atooth brushing demonstration method was effective in improving brushing skills (p